Metallurgical aspects of the iron bloom formation – experiments in side-blast forge - Thiele, Ádám; Hári, László (Bányászati és Kohászati Lapok, 2024)
In this paper, a model experiment is presented, in which iron bloom is extraced from small iron nails charged into a side-blast charcoal fueled forge (copy of medieval forges). On the basis of the observations and material analyses of samples taken during the experiments, conclusions are drawn regarding the metallurgical aspects of the iron bloom formation during the medieval iron smelting.